Interconnection of the Gut-Skin Axis in NC/Nga Mouse with Atopic Dermatitis: Effects of the Three Types of Bifidobacterium bifidum CBT-BF3 (Probiotics, Postbiotics, and Cytosine-Phosphate-Guanine Oligodeoxynucleotide) on T Cell Differentiation and Gut Microbiota - Kim, Gwang Il; Jeong, Hwa Yeong; Kim, In Sung; Lee, Seung Ho; Kim, Sung Hak; Moon, Yang Soo; Cho, Kwang Keun (Food science of animal resources, 2024)
The gut microbiota is an immune system regulator in the gut-skin axis. Dysfunctional interactions between the gut microbiota and the gut immune system can lead to the development of skin diseases such as atopic dermatitis (AD). Probiotics and postbiotics positively affect the balance of the gut microbiota, immune regulation, protection against pathogens, and barrier integrity. This study investigated the effects of probiotic , postbiotic (heat-killed), and cytosine-phosphate-guanine oligodeoxynucleotide (CpG ODN) on the gut microbiota and T cell differentiation in NC/Nga mice induced with AD. 2,4-Dinitrochlorobenzene-induced AD mice had an increased SCORing atopic dermatitis-index and increased mRNA expression levels of Th2 and Th17 cell transcription factors and cytokines, and ( ) cytokine in their mesenteric lymph nodes (mLNs; p<0.05). However, oral administration of the three types of (probiotics, postbiotics, CpG ODN) to AD mice decreased the mRNA expression levels of Th2 and Th17 cell transcription factors and cytokines as well as cytokine. They increased the mRNA expression levels of regulatory T (Treg) cell transcription factor and cytokine, , and genes (p<0.05). These effects were more noticeable in the mLNs than in the spleen. In addition, AD mice showed a decrease in , spp., , , and (p<0.05). However, oral administration of the three types of increased spp., spp., , and spp. (p<0.05).